Comparison of Notary Deed and Certificate of Relinquishment of Land Rights by The Head of The Land Office in The Process of Releasing Land Rights for Private Interests - Hariani, Hesti; Adjie, Habib (State of Islamic Institute Langsa, 2023)
Requests for Land Release by private parties often lead to disputes. This is a derivative of the difference in legal force of the proof of the Deed of Release of Land Rights made by the Head of the Land Office and the Statement of Release of Land Rights made by the Head of the Land Office. This study aims to obtain empirical knowledge about the comparison between notarial deeds and Certificate of Release of Land Rights by the Head of the Land Office in the process of releasing land rights for private interests. This article is classified as literature research with a qualitative approach. The method used is an empirical juridical study. The results of the study explained that in the process of proving the release of land rights for personal interests, a notarial deed was used which was an Authentic Deed and a statement made before the Head of the Land Office.